Pengaruh Intellectual Capital Terhadap Kinerja Keuangan Pada Bank Pembangunan Daerah di Indonesia - Isma Dewi Br. Panjaitan; Isfenti Sadalia (Universitas Sumatera Utara, 2013)
ABSTRACT This research to determine the influence of intellectual capital of financial performance on Regional Development Bank in Indonesian. The independent variable in this research is the intellectual capital as measured by VAICTM and the dependent variable is financial performance as measured by Return On Assets (ROA), BOPO, Asset Turn Over (ATO) and Growth (GR).The obtained of data from18 Regional Development Bank publisher a complete the financial of reports for 5-year periods, it starting from 2008 until 2012. This research uses The Pulic Model (Value Added Intellectual Capital Coefficient-VAICTM) as the efficiency measure of intellectual capital component. The method used is descriptive analysis and simple regression analysis with use SPSS for windows to process. The result show that intellectual capital (VAICTM) has a positive and not significant to financial performance regional development bank, except BOPO and GR, intellectual capital (VAICTM) has a positive and not significant to financial performance regional development bank in the coming period, except BOPO and intellectual capital growth (ROGIC) has a positive and not significant to financial performance regional development bank except BOPO and GR. Keywords : intellectual capital, VAICTM, Return On Assets (ROA), BOPO, Assets Turn Over (ATO), Growth (GR), ROGIC